Characterisation of orange peel on highly polished steel surfaces. (July 2015) - Miranda-Medina, M. L.; Somkuti, P.; Bianchi, D.; Cihak-Bayr, U.; Bader, D.; Jech, M.; Vernes, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The surface quality of high gloss polished steel sheets with respect to 'orange peel' is studied. This is motivated by the fact that workpieces are ranked solely on the visual appearance of finished surfaces according to the observed degree of orange peel. Here, to quantify the degree of orange peel, surface topographies of industrial samples are acquired by means of phase shifting interferometry, from which various surface roughness parameters are calculated. These parameters are related to qualitative aspects of the surface using the Spearman's rank correlation coefficient. Two surface roughness parameters were identified as necessary for the evaluation of orange peel, suggesting that traditional methods can be replaced with suitable parameters that improve quality control procedures at the industry.